Ti50Ni48.7Fe1.3 shape memory alloy and preparation method thereof
By adjusting the element composition in the shape memory alloy and using vacuum arc smelting technology, Ti50Ni48.7Fe1.3 shape memory alloy was prepared, which solved the problems of large thermal hysteresis and high energy dissipation of existing alloys, and achieved zero thermal hysteresis and high energy dissipation. Conversion efficiency.
Patent Information
- Application Number
- CN202411664515.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
Smart Images

Figure CN119464837A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials and relates to Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy. The present invention also relates to a method for preparing the shape memory alloy. Background Art
[0002] Shape Memory Alloys (SMA) is a type of smart alloy with shape memory effect (SME) and superelasticity (SE). Its main feature is that after a large deformation is applied to it, it can almost completely recover to its original shape when heated to a certain temperature. This is because during the deformation process of the shape memory alloy, the thermoelastic martensitic phase transformation generated inside the material produces a low-temperature phase (martensite) that can undergo a reversible transformation to a high-temperature phase (austenite) when heated.
[0003] Since the crystal structure and unit cell volume of the alloy will change before and after the martensitic phase transformation, the shape memory alloy has a large thermal hysteresis. Thermal hysteresis is one of the important phase transformation characteristics of shape memory alloys and is closely related to its functional characteristics. Among them, narrow thermal hysteresis alloys have high cycle stability and can be used to make micro-electromechanical system actuators and solid-state phase change refrigeration media. Therefore, designing narrow thermal hysteresis shape memory alloys has important practical value. Improving the martensitic phase transformation hysteresis problem of shape memory alloys has become a major problem for shape memory alloys to move towards application fields.
[0004] The temperature hysteresis of NiTi shape memory alloy is related to the added third element. By adjusting the alloy element composition and alloy component ratio, the functional properties such as thermal hysteresis of the alloy can be adjusted to meet different application requirements. At present, shape memory alloys have large thermal hysteresis, high energy dissipation and low conversion efficiency. Studies have shown that the addition of Fe elements affects the phase change path of shape memory alloys. Although the addition of Fe elements to NiTi shape memory alloys has a significant effect on the low-temperature application of NiTi-based alloys and shows unique advantages, shape memory alloys with zero thermal hysteresis at room temperature, low price and good cycle stability have not yet been obtained. Summary of the invention
[0005] The object of the present invention is to provide a Ti 50 Ni 48.7 Fe 1.3 The shape memory alloy solves the problems of large thermal hysteresis, large energy dissipation and low conversion efficiency of the shape memory alloy in the prior art.
[0006] Another object of the present invention is to provide the above Ti 50 Ni 48.7 Fe 1.3Preparation method of shape memory alloy.
[0007] The technical solution adopted by the present invention is: Ti 50 Ni 48.7 Fe 1.3 The shape memory alloy is composed of the following raw material components according to atomic percentage: 50 at % Ti, 48.7 at % Ni, and 1.3 at % Fe.
[0008] Another technical solution adopted by the present invention is: Ti 50 Ni 48.7 Fe 1.3 The preparation method of the shape memory alloy is specifically implemented according to the following steps: Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a vacuum arc melting furnace; Step 2, striking an arc in an argon environment, adjusting the arc current after the arc is stable, and starting smelting to obtain an ingot; Step 3, turn off the arc gun, turn over the ingot in the smelting furnace, and repeat step 2; Step 4: After repeated smelting for several times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample to cool down to obtain the ingot Ti. 50 Ni 48.7 Fe 1.3 .
[0009] Another technical solution of the present invention is also characterized in that: Step 2 is as follows: In an argon environment, the smelting sample is adjusted to the bottom of the arc gun, and the arc gun is adjusted to a distance of 2 to 3 mm from the smelting sample to start the arc. After the arc is stable, the arc current is adjusted to start smelting to obtain an ingot.
[0010] The pressure of argon during the smelting process is 0.08MPa.
[0011] Adjust the arc current to 250~350A.
[0012] After starting smelting, the raw materials are kept in a molten state for 65 to 75 seconds, and then the position of the arc gun is adjusted to melt and obtain an ingot.
[0013] Adjust the arc gun to a distance of 20~30mm from the melting sample.
[0014] In step 4, the smelting process is repeated 5 to 7 times.
[0015] The beneficial effects of the present invention are: The present invention 50 Ni 48.7 Fe 1.3 The shape memory alloy includes Ti, Ni and Fe. Due to the influence of Fe on the alloying of Ti-Ni alloy, the above alloy has the coexistence of B19' phase and R phase, so that the alloy exhibits the performance characteristics of zero hysteresis. 50 Ni 48.7 Fe 1.3 The preparation method of shape memory alloy is simple and low-cost. The alloy has zero thermal hysteresis and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The Ti prepared in Example 4 of the present invention 50 Ni 48.7 Fe 1.3 DMA diagram of shape memory alloy; Figure 2 The Ti prepared in Example 4 of the present invention 50 Ni 48.7 Fe 1.3 DSC graph of shape memory alloy. DETAILED DESCRIPTION
[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0018] The present invention 50 Ni 48.7 Fe 1.3 The shape memory alloy is composed of the following raw material components according to atomic percentage: 50 at % Ti, 48.7 at % Ni, and 1.3 at % Fe.
[0019] The present invention 50 Ni 48.7 Fe 1.3 The preparation method of the shape memory alloy is specifically implemented according to the following steps: Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a vacuum arc melting furnace; Step 2, under a 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to a distance of 2-3mm from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 250-350A, start smelting, first keep the raw material in a molten state for 65-75s, then adjust the arc gun to a distance of 20-30mm from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process 5 to 7 times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain the ingot Ti. 50 Ni 48.7 Fe 1.3 .
[0020] In a general martensitic phase transformation, the incompatibility between the martensitic phase and the parent phase will cause lattice defects in the phase transformation process, resulting in a stress transition layer between the two phases and a lagging energy barrier. The addition of Fe in the method of the present invention causes the phase transformation here to transition from a first-order discontinuous phase transformation to a continuous phase transformation.
[0021] When the Fe content is 1.3, the system undergoes a two-step transition from B2 to R and then to B19′. Compared with the one-step transition, the lattice compatibility of the system is improved, the stress transition layer is basically eliminated, and therefore it has a smaller thermal hysteresis.
[0022] Before the formation of B19′ martensite, R martensite phase appears, mainly due to the appearance of Ti3Ni4 precipitates. Because the formation of B19′ martensite is accompanied by a large phase transformation strain, the presence of Ti3Ni4 precipitates has a huge inhibitory effect on the formation of B19′ martensite. On the contrary, the formation of R martensite is accompanied by a small phase transformation strain, and the presence of these precipitates basically has no effect on the formation of R martensite phase. Therefore, R phase often corresponds to a smaller thermal hysteresis.
[0023] Example 1 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to 2mm away from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 250A, start smelting, keep the raw material in a molten state for 65s, then adjust the arc gun to 20mm away from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process six times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0024] Example 2 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to 2mm away from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 270A, start smelting, keep the raw material in a molten state for 70s, then adjust the arc gun to 30mm away from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process five times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0025] Example 3 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to 2mm from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 320A, start smelting, keep the raw material in a molten state for 70s, then adjust the arc gun to 25mm from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process seven times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0026] Example 4 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to 2mm from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 320A, start smelting, keep the raw material in a molten state for 75s, then adjust the arc gun to 25mm from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process six times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0027] The shape memory alloy obtained in Example 4 was cut into thin slices of 5 mm × 5 mm × 1 mm, solution treated at 1270 K for 1 h in a vacuum quartz tube, then water quenched, mechanically polished with sandpaper, the surface was cleaned, and then the obtained shape memory alloy was tested: The dynamic mechanical analysis (DMA) test was carried out using DMA Q800. The test mode was single cantilever beam mode, the fixture length was 35 mm, the 6 test frequencies were 0.2 Hz, 0.4 Hz, 1 Hz, 4 Hz, 10 Hz, and 20 Hz, and the heating and cooling rates were 2 K / min. The test results are shown in the figure. Figure 1 As shown, the lower part of the figure shows the change of internal friction, and the upper part shows the change of storage modulus. The results show that the internal friction peak of martensitic transformation does not depend on the measurement frequency change.
[0028] Differential Scanning Calorimetry (DSC) was performed with a heating / cooling rate of 10 K / min. Figure 2 As shown, the thermal hysteresis of the alloy is calculated using the tangent method, and the thermal hysteresis (ΔT) is 0.27K, which means that Ti with zero thermal hysteresis is prepared. 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0029] Example 5 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to 3mm from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 350A, start smelting, keep the raw material in a molten state for 75s, then adjust the arc gun to 20mm from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process five times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0030] Example 6 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the distance between the arc gun and the smelting sample to 3mm, start the arc, and after the arc is stable, adjust the arc current to 300A, start smelting, keep the raw material in a molten state for 75s, then adjust the distance between the arc gun and the smelting sample to 30mm, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process six times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0031] Example 7 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to 2mm away from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 330A, start smelting, keep the raw material in a molten state for 70s, then adjust the arc gun to 20mm away from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process six times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0032] Example 8 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the arc gun to 3mm from the smelting sample, start the arc, and after the arc is stable, adjust the arc current to 280A, start smelting, keep the raw material in a molten state for 75s, then adjust the arc gun to 30mm from the smelting sample, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process seven times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0033] Example 9 Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the distance between the arc gun and the smelting sample to 3mm, start the arc, and after the arc is stable, adjust the arc current to 310A, start smelting, keep the raw material in a molten state for 65s, then adjust the distance between the arc gun and the smelting sample to 28mm, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process six times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
[0034] Example 10 Step 1: Follow Ti 50 Ni 48.7 Fe1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a smelting furnace; Step 2, under 0.08MPa argon environment, adjust the smelting sample to the bottom of the arc gun, adjust the distance between the arc gun and the smelting sample to 3mm, start the arc, and after the arc is stable, adjust the arc current to 300A, start smelting, keep the raw material in a molten state for 70s, then adjust the distance between the arc gun and the smelting sample to 25mm, and smelt to obtain an ingot; Step 3, turn off the arc gun, use a mechanical rod to turn the ingot over in the smelting furnace, and repeat step 2; Step 4: After repeating the smelting process six times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample obtained in step 3 to cool down to obtain Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy.
Claims
1. Ti 50 Ni 48.7 Fe 1.3 Shape memory alloy, characterized in that The raw material components are composed of the following in atomic percentage: 50 at % Ti, 48.7 at % Ni, and 1.3 at % Fe.
2. Ti 50 Ni 48.7 Fe 1.3 A method for preparing a shape memory alloy, characterized in that: Follow the steps below to implement it: Step 1: Follow Ti 50 Ni 48.7 Fe 1.3 Weigh the raw materials Ti, Ni and Fe in an atomic ratio of , and put the raw materials into a vacuum arc melting furnace; Step 2, striking an arc in an argon environment, adjusting the arc current after the arc is stable, and starting smelting to obtain an ingot; Step 3, turn off the arc gun, turn over the ingot in the smelting furnace, and repeat step 2; Step 4: After repeated smelting for several times, turn off the arc gun, turn off the power of the smelting furnace, and wait for the sample to cool down to obtain the ingot Ti. 50 Ni 48.7 Fe 1.3 .
3. Ti according to claim 2 50 Ni 48.7 Fe 1.3 A method for preparing a shape memory alloy, characterized in that: Step 2 is as follows: In an argon environment, the smelting sample is adjusted to the bottom of the arc gun, and the arc gun is adjusted to a distance of 2 to 3 mm from the smelting sample to start the arc. After the arc is stable, the arc current is adjusted to start smelting to obtain an ingot.
4. Ti according to claim 3 50 Ni 48.7 Fe 1.3 A method for preparing a shape memory alloy, characterized in that: The pressure of argon during the smelting process is 0.08MPa.
5. Ti according to claim 3 50 Ni 48.7 Fe 1.3 A method for preparing a shape memory alloy, characterized in that: Adjust the arc current to 250~350A.
6. Ti according to claim 3 50 Ni 48.7 Fe 1.3 A method for preparing a shape memory alloy, characterized in that: After starting smelting, the raw materials are kept in a molten state for 65 to 75 seconds, and then the position of the arc gun is adjusted to melt and obtain an ingot.
7. Ti according to claim 6 50 Ni 48.7 Fe 1.3 A method for preparing a shape memory alloy, characterized in that: Adjust the arc gun to a distance of 20~30mm from the melting sample.
8. Ti according to claim 1 50 Ni 48.7 Fe 1.3 A method for preparing a shape memory alloy, characterized in that: In step 4, the smelting process is repeated 5 to 7 times.